Gender and the Performance of Informal Sector Enterprises - Jayeola, Olakunle; Sidek, Shafie; Owoeye, Idowu; Kazeem, Yusau Kunle (European Scientific Journal, ESJ, 2020)
The objective of the study was to examine whether female and maleled informal businesses differ in terms of performance. Using a simple random sampling, 250 paper questionnaires were distributed by hand to small and micro enterprises, out of which 90 responses were gathered from owners and managers of informal enterprises. The Upper Echelon Theory (UET) serves as the main theory that underpins this study. Mann-Whitney test was employed to test the study’s hypotheses. The findings of the study revealed that there was a significantly equal relationship between gender and profit. Sales and gender performance however indicated a non-significant relationship. Female-led enterprises had a significantly higher employees’ growth than male-led enterprises. Overall, female outperformed male in the informal sector based on employees’ growth which is an indication of female’s lenient, empathetic and good leadership style than male.